Professional Development Of EFL Teachers in Implementing Deep Learning-Oriented Kurikulum Merdeka - Setya Rochmad Catur Cahyadi; Ardiasih, Lidwina Sri; Pratiwi, Widya Rizky (Universitas Maritim Raja Ali Haji (UMRAH), 2025)
This study investigates the professional development and support systems required to enhance junior high school EFL teachers’ readiness in implementing the deep learning-oriented Kurikulum Merdeka in Bintan Regency, Indonesia. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis. Findings indicate that while teachers demonstrated moderate to high readiness in effort, willingness, and capacity, sustaining deep learning practices was constrained by limited professional development opportunities, infrastructural challenges, and insufficient systemic support. Teachers identified the need for continuous practice-based professional development, access to digital resources, peer collaboration through MGMP (teacher working groups) and school-based learning communities, and structured mentoring programs. Systemic supports such as improved infrastructure, manageable class sizes, and context-sensitive policy implementation were also considered crucial. The study underscores the importance of aligning professional development initiatives with the real-world challenges faced by teachers in diverse educational contexts, ensuring that the implementation of curriculum reform is both sustainable and equitable.